Preparation of recombinant fibronectin fragments for functional and structural studies. - Staunton, D; Millard, C; Aricescu, A; Campbell, I (2009)
Fibronectin, an ubiquitous extracellular matrix (ECM) glycoprotein, plays a major role in fundamental biological processes such as cell adhesion and migration, maintenance of normal cell morphology, cytoskeletal organization, and cell differentiation. Fibronectin is constructed from three types of independently folding protein module (Fn1, Fn2, and Fn3) and is found as a Fibrillar network in the ECM where it interacts with other ECM components and provides anchorage sites for cell surface integrin receptors. The mosaic nature of fibronectin permits it to be analyzed by a "dissection" strategy, where protein fragments generated by recombinant expression in E. coli, P. pastoris, and human cell lines are employed in structural and functional investigations. We describe methods suitable for the production of various fibronectin fragments for study by a variety of techniques including crystallography and electron microscopy but special mention is made of methods suitable for the production of samples for NMR studies.